Mangrove ecosystems in Sebongkok Island, District of Selat Nasik, Belitung Timur Regency - Irma Akhrianti (Jurusan Akuakultur, Universitas Bangka Belitung, 2016)
Sebongkok Island is one of a small island with a high potential mangrove resource with an equitable distribution. Communities around the Sebongkok Island used it inefficiently. The problems might because of lacking information (database) regarding the assessment of inventory, identification and mangrove structure vegetation, both derived from the research of academics, NGOs, government agencies and other institutions that engaged in the field of sustainability environment. Therefore, this research is important for mangrove sustainability. This study aims to: 1) determine the diversity and density of the mangrove species at the SebongkokIsland and its relation with abiotic components, 2) determine the status and condition of mangrove ecosystem on the Sebongkok Island. Our study revealed that the mangrove vegetation found in Sebongkok Island consists of 7 mangrove species, 5 families. The mangrove species that the most dominate and play an important role was R. apiculata, R. stylosa, and R. mucronata.